Avaliação dos efeitos da contaminação por derramamento de óleo no Atlântico Sudoeste Tropical por meio do uso de organismos planctônicos - Silva, Alef Jonathan da (Universidade Federal de São Carlos, 2023)
The growing global demand for oil has led to an increase in the exploration and maritime transportation of this resource, resulting in higher risks of oil spill accidents. These accidents can cause serious environmental damage and contamination in the affected sites, as happened in the coastal region of Brazil in 2019, when more than 3,000 km of coastal ecosystems were affected. Oil spills pose a great danger to marine biota, with planktonic organisms being one of the groups most affected by the toxic compounds present in the oil. In this thesis, several investigations were conducted with the aim of understanding the effects of the 2019 oil spill in the Southwest Atlantic on planktonic organisms and the ecological implications. For this, a bibliometric analysis was initially carried out to assess the interest of the scientific community on this event, identify study gaps, relevant works and researchers involved in investigations related to the oil spill. Then, laboratory experiments were conducted to evaluate the effects of toxic compounds present in the oil on planktonic organisms. The microalga Isochrysis galbana, when exposed to the polycyclic aromatic hydrocarbons (PAHs) present in the spilled oil, showed a decrease in growth rate, an increase in chlorophyll-a concentration in the cells, an increase in cell volume, and increased vulnerability to predation. In addition, a primary consumer, Brachionus plicatilis, was also impacted during exposure, with increased mortality and reduced filtration and ingestion rates. The environmental risk analysis indicated that the concentrations of PAHs obtained from the spilled oil may represent a serious problem for the tested species and other species. In addition, a field investigation assessing the copepod community showed a significant increase in mortality of these organisms when the oil reached the environment. In a microcosm experiment, the copepod community exposed to different concentrations of PAHs showed a dose-response relationship, with higher mortality at higher concentrations. These results indicate that oil spills can cause significant impacts on the productivity and structure of planktonic communities, posing a potential risk to upper trophic levels and, in general, to the stability of marine ecosystems. The thesis therefore contributes to the understanding of ecological impacts generated by oil spill events in marine environments.
Assessment of the effects of oil spill contamination in the Tropical Southwest Atlantic through the use of planktonic organisms
Keywords: Zooplâncton; Fitoplâncton; Toxicidade; Derramamento de óleo; HPAs; Zooplankton; Phytoplankton; Toxicity; Oil spill; HPAs; CIENCIAS BIOLOGICAS::ECOLOGIA